(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Recent studies in magnetic resonance imaging (MRI) aim to improve image quality while reducing scan time. Electrical current injection in the form of magnetic resonance electrical impedance tomography (MREIT) is believed to be affecting image quality and scan time thus can improve the possibility of becoming a non-chemical contrast agent in MRI. This study will observe and analyze the effect of electrical current injection on a phantom object to determine whether there is a different tissue image intensity. A thigh of lamb was used as a biological tissue phantom. The scan was performed on both T1and T2-weighted without and with an electrical current injection of 0.5 mA Electrical current injection decreased mean of tissue image intensity on T1-weighted images on both muscle (1759 vs 794) and bone (2752 vs 1550) (p<0.05). On the other hand, the electrical current increased mean of tissue image intensity on T2-weighted images on both muscle (303 vs 897) and bone (579 vs 1499) (p<0.05). There is also a difference in tissue image intensity on both T1 and T2-weighted images with and without electrical current injection on bone and muscle. The implication of this difference in image quality is a subject for further study.